Pharmacokinetic/Pharmacodynamic Integration of Doxycycline Against Mycoplasma hyopneumoniae in an In Vitro Model - Zhang, Huilin; Mao, Chunxiao; Li, Jinju; Huang, Zilong; Gu, Xiaoyan; Shen, Xiangguang; Ding, Huanzhong (Frontiers in Pharmacology, 2019)
Doxycycline is a broad-spectrum antibacterial drug. It is used widely to treat diseases caused by Mycoplasma species. We investigated the antibacterial activity of doxycycline against the Mycoplasma hyopneumoniae (M. hyopneumoniae) strain ATCC25934. The minimum inhibitory concentration (MIC) of doxycycline against M. hyopneumoniae determined by a micro-dilution method was 0.125 μg/mL. Static time–kill curves with constant drug concentrations (0–64 MIC) showed that a bacteriostatic effect occurred if the doxycycline concentration reached 4 MIC. Doxycycline produced a maximum anti-mycoplasmal effect (reduction of 2.76 log10CFU/mL) at 64 MIC within 48 h. The effect of doxycycline against M. hyopneumoniae was analyzed by a sigmoid Emax model, and there was high correlation between the kill rate and doxycycline concentration (R2 = 0.986). A one-compartment open model with first-order absorption was established, and was used to simulate doxycycline pharmacokinetics in porcine plasma. The dynamic time–concentration curve showed that the area under the curve at 24 h (AUC24h) and Cmax （peak concentration） after each drug administration was 1.78–48.4 μg•h/mL and 0.16–3.41 μg/mL, respectively. The reduction of M. hyopneumoniae (log10CFU/mL) for 1, 2.5, 5, 7.5, 10, 15, 20, and 30 mg/kg body weight was 0.16, 1.29, 1.75, 2.94, 3.35, 3.91, 4.35, and 5.77, respectively, during the entire experiment, respectively. When the dose was >10 mg/kg body weight, continuous administration for 3 days could achieve a bactericidal effect. The correlation coefficient of AUC24 h/MIC, Cmax/MIC, and %T >MIC (the cumulative percentage of time over a 24h period that the drug concentration exceeds the MIC) with antibacterial effect was 0.917, 0.923, and 0.823, respectively. Doxycycline showed concentration-dependent activity, and the value of AUC24h/MIC and Cmax/MIC required to produce a drop of 1 log10CFU/mL was 164 h and 9.89, respectively.